ANALISIS PENENTU SEKTOR-SEKTOR PEREKONOMIAN TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TENGAH - Wanda Astika Noviyanti; Sishadiyati Sishadiyati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to determine the leading sector, changes and shifts in economic sectors, the strength of growth and employment in the leading sector in Central Java province. The methods used in this study are, Analysis of LQ, SS, MRP, and RTK. The results of LQ analysis there are 7 basic sectors of the processing industry memilihas the highest base value of 1.63. The results of the SS analysis showed that there are 12 sectors that have changed and the processing industry hasai perubaha high contribution of 6 395.78, while sedanthe information and communication sector has the highest shift value of 7 793.58. than the sector. The results of MRP analysis showed that the transportation and warehousing sector hasribusi nilai a high ter valuetinggi of 4.18 dicompared to other sectors. And the results of the RTK analysis there are two sectors that have the highest value above 10%, namely the water supply sector, waste treatment, waste and recycling of 18.86 and the Real Estate sector of 29.67, these two sectors are able to absorb more labor compared to other sectors in Central Java province.